Sealing Ability of Orthograde MTA and CEM Cement in Apically Resected Roots Using Bacterial Leakage Method - Moradi, Saeed; Disfani, Reza; Ghazvini, Kiarash; Lomee, Mahdi (Iranian Endodontic Journal, 2013)
Introduction: The aim of this in vitro study was to determine the sealing ability of orthograde ProRoot mineral trioxide aggregate (MTA) and calcium enriched mixture (CEM) cement as root-end filling materials. Materials and Methods: Fifty four extracted single-rooted human teeth were used. The samples were randomly divided into 3 experimental groups. In group A and B, 4 mm of WMTA and CEM cement were placed in an orthograde manner and 3 mm of apices were resected after 24 hours. In group C the apical 3 mm of each root was resected and the root-end prepared with ultrasonic tips to a depth of 3 mm and subsequently, then filled with MTA. The apical sealing ability was performed with bacterial leakage method. Statistical analysis was carried out with Chi-square test. Results: There were no significant differences in the extent of bacterial leakage between the three experimental groups (P>0.05). Conclusion: Based on the limitations of this in vitro study, we concluded that MTA and CEM cement can be placed in an orthograde manner when there is a potential need for root-end surgery.